Agreement Between Postnatal Meconium Drug Screen and Maternal Urine Drug Screen for Drug Use During Pregnancy [16C]. (May 2017) - Debbink, Michelle; Smith, Shannon; Langen, Elizabeth
Abstract : INTRODUCTION: Postnatal meconium drug screen (MDS) is the test of choice for suspected fetal exposure to drugs, theoretically revealing exposures up to 3-6 months antenatally. The degree to which MDS correlates with maternal urine drug screens (UDS) is not well understood. Both test results have significant implications for families. We sought to assess agreement between antenatal UDS and postnatal MDS. METHODS: We included women with singleton pregnancies between 2009-2016 at a specialized clinic for substance use in pregnancy. Exclusions included delivery at another institution. Using MDS as an imperfect reference standard, the overall percent agreement (OPA), positive and negative percent agreement (PPA and NPA), and Cohen's kappa for UDS were calculated for cannabinoids (THC) and cocaine. Tests positive for multiple drugs were descriptively compared. RESULTS: Among 108 pregnancies, most patients were white, with mean age of 28.6y. Approximately 50% had addictive disorders, while the remainder had chronic pain. For THC, the OPA was 83.3%, Cohen's kappa was 0.58 (95%C.I. 0.40-0.77), PPA was 67.7%, and NPA was 89.6%. For cocaine, OPA was 91.7%, kappa, 0.59 (95%C.I. 0.40-0.78), PPA, 61.5%, and NPA, 61.5%. Thirty-four patients had multiple drugs on MDS or UDS. Of these, 7 (21%) had negative UDS with positive MDS; 2 (6%) had negative MDS with positive UDS. Concordant tests occurred in 11 cases (32.3%), and partially concordant tests in 11 cases (32.2%). CONCLUSION: The agreement between postnatal MDS and antenatal UDS is moderate. Disagreement between positive screens affects 30-40% of tests. These inconsistencies should be considered in patient care decisions and policies.